Proposal of a New Method for Controlling the Thaw of Permafrost around the China–Russia Crude Oil Pipeline and a Preliminary Study of Its Ventilation Capacity - Yapeng Cao; Guoyu Li; Gang Wu; Dun Chen; Kai Gao; Liyun Tang; Hailiang Jia; Fuqiang Che (Water, 2021)
The China–Russia crude oil pipeline (CRCOP) has been in operation for over ten years. Field observation results have shown that a thaw bulb has developed around the CRCOP which expands at a rate of more than 0.8 m∙a−1 in depth. In view of the deficits of existing measures in mitigating permafrost thaw, a new control method is proposed based on active cooling. According to the relationship between total pressure loss and the driving force of natural ventilation, the wind speed in a U-shaped air-ventilation pipe around the CRCOP is calculated. By analyzing the theoretical calculation and numerical analysis results, it is found that the influence of thermal pressure difference on the natural ventilation of the structure can be negligible, and the influences of resistance loss along the pipe and local resistance loss in the pipe are similarly negligible. Exhaust elbows greatly improve the ventilation performance of the U-shaped air-ventilated pipe. This study developed a novel structure around warm-oil pipelines in permafrost for mitigating thaw settlement along the CRCOP and other similar projects across the world.